Tourist satisfaction towards Kota Kinabalu, Sabah using importance-performance analysis (IPA) as a tool to determine urban ecotourism potential - Nattana Simon; Fiffy Hanisdah Saikim; Awangku Hassanal Bahar Pengiran Bagul; Nor Akmar Abdul Aziz (Journal of Tropical Biology and Conservation, 2020)
The Importance-Performance Analysis (IPA) is widely used in many fields of study as it produces simple and straightforward results. However, it is rarely used by managers of ecotourism and urban green spaces. Importance-Performance Analysis (IPA) was adopted from a destination perspective to understand industry demand. This study explores the visitors’ satisfaction level on ecotourism attributes i.e. attraction, urban green spaces and accessibility that affect tourist satisfaction towards Kota Kinabalu, Sabah, Malaysia using IPA scheme. A total of 384 tourists to Kota Kinabalu were provided with a list of environmental features and asked to rate the importance of and satisfaction with each attribute. IPA was performed to compare mean scores and identify areas of concern. The analysis identified eight (8) attributes which were applauded with excellent performance on highly important features and should maintain its competitiveness as a tourist destination. Six (6) attributes resulted under the poor performance on an extremely important category; indicates the areas that should be given improvement interventions, while four (4) attributes were identified as possible overkill that implies divergences of resources elsewhere are needed. Finally, six (6) attributes faired as low in priority and effort may not be necessary on those features. Although six (6) out of 24 attributes were found to be less advantageous, an interview simultaneously conducted during the survey however found that 97% of respondents perceived that Kota Kinabalu city has the potential as an Urban Ecotourism destination. This study resulted in some findings for those at managerial level to pursue and areas that should be improved as it provides a greater understanding on the Urban Ecotourism potential in Kota Kinabalu industry, by using the Importance-Performance Analysis (IPA) tool as it facilitates the interpretation of data. This study fosters that ecotourism product does exist in Kota Kinabalu city, and steer the industry towards sustainable development in urban centres.